The Socio-Economic Factors Influencing Sugar-Sweetened Beverages (SSB’s) Consumption in Household of DKI Jakarta Province in 2020 - Muhammad Gozali Yahya; Arya Candra Kusuma; Norvan Bagus Ramadhan (Politeknik Statistika STIS, 2023)
Non-communicable diseases (NCDs) are responsible for causing 41 million deaths annually, constituting approximately 74% of all global fatalities. One of the key factors contributing to the elevated risk of NCD’s is the excessive consumption of sugary beverages, which encompass a variety of liquid products containing added sugars. This research endeavor seeks to identify the socioeconomic factors that perform in shaping the consumption patterns of sugary beverages within households residing in Province of DKI Jakarta. This study using data from the 2020 Susenas survey, contain a total of 5,456 sampled households. Binary logistic regression is used for modelling whether households had consumed sugary beverages during the preceding week or not. Variables such as marital status, gender, age, educational attainment, employment status of the household head, as well as internet accessibility, economic status, internet usage motives, and household size, were found to influence the likelihood of consuming sugar-sweetened beverages (SSBs) in DKI Jakarta Province. Based on these findings, it is recommended to enhance the use of the internet for promoting healthy lifestyles.